Optimisation of compact laser driven accelerator X-ray sources for industrial imaging applications - Symes,DR; Brenner,CM; Rusby,DR; Armstrong,C; Thornton,C; Bourgeois,N; Katzir,Y; Gregory,CD; Neely,D; Rajeev,PP; Allott,R; Wood,JC; et al. (2018)
Compact laser-driven electron accelerators can produce coherent x-ray beams with high brightness, small source-size and femtosecond duration. We will discuss the suitability of these sources to address challenges in industrial imaging.